Understanding Scarlett Thomas’ fiction: the anti-heroic heroine - Mélody Sánchez (The Grove, 2016)
In 2004 Scarlett Thomas published PopCo, the third volume of a trilogy devoted to contemporary pop culture and its effects. Through the experiences of her heroine, Alice Butler, we get to know the inner struggle of someone who inhabits a daily routine of an inconsistent occupation and lifestyle. This particular character, remarkable for her interest in unsolved riddles and strong dissatisfaction with the 21st  century society, is but the accumulation of common features of Thomas’ previous figures, as well as the inspirational source for her later novels. Consolidated as an archetype, Thomas also proposes her female character as an alternative role model to the typical heroine. This paper aims to analyse the character of Alice Butler as heroine and anti-heroine in the context of her novel, together with the precursors and descendants, and the reasons why she serves as a role model.